Extracellular proteolytic activity and amino acid production by lactic acid bacteria isolated from Malaysian foods - Toe, Cui Jin; Foo, Hooi Ling; Loh, Teck Chwen; Mohamad, Rosfarizan; Abdul Rahim, Raha; Idrus, Zulkifli (MDPI, 2019)
Amino acids (AAs) are vital elements for growth, reproduction, and maintenance of organisms. Current technology uses genetically engineered microorganisms for AAs production, which has urged the search for a safer food-grade AA producer strain. The extracellular proteolytic activities of lactic acid bacteria (LAB) can be a vital tool to hydrolyze extracellular protein molecules into free AAs, thereby exhibiting great potential for functional AA production. In this study, eight LAB isolated from Malaysian foods were determined for their extracellular proteolytic activities and their capability of producing AAs. All studied LAB exhibited versatile extracellular proteolytic activities from acidic to alkaline pH conditions. In comparison, Pediococcus pentosaceus UP-2 exhibited the highest ability to produce 15 AAs extracellularly, including aspartate, lysine, methionine, threonine, isoleucine, glutamate, proline, alanine, valine, leucine, tryptophan, tyrosine, serine, glycine, and cystine, followed by Pediococcus pentosaceus UL-2, Pediococcus acidilactici UB-6, and Pediococcus acidilactici UP-1 with 11 to 12 different AAs production detected extracellularly. Pediococcus pentosaceus UL-6 demonstrated the highest increment of proline production at 24 h of incubation. However, Pediococcus acidilactici UL-3 and Lactobacillus plantarum I-UL4 exhibited the greatest requirement for AA. The results of this study showed that different LAB possess different extracellular proteolytic activities and potentials as extracellular AA producers.